2013
DOI: 10.1186/1743-422x-10-164
|View full text |Cite
|
Sign up to set email alerts
|

A remarkable synergistic effect at the transcriptomic level in peach fruits doubly infected by prunus necrotic ringspot virus and peach latent mosaic viroid

Abstract: BackgroundMicroarray profiling is a powerful technique to investigate expression changes of large amounts of genes in response to specific environmental conditions. The majority of the studies investigating gene expression changes in virus-infected plants are limited to interactions between a virus and a model host plant, which usually is Arabidopsis thaliana or Nicotiana benthamiana. In the present work, we performed microarray profiling to explore changes in the expression profile of field-grown Prunus persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 68 publications
1
36
1
Order By: Relevance
“…This family includes four members, and the type species is the Avocado sunblotch viroid (ASBVd). That said, recently, the Peach latent mosaic viroid (PLMVd) has received more attention (Herranz et al, 2013;Navarro et al, 2012;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This family includes four members, and the type species is the Avocado sunblotch viroid (ASBVd). That said, recently, the Peach latent mosaic viroid (PLMVd) has received more attention (Herranz et al, 2013;Navarro et al, 2012;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other studies have shown that diverse host genes exhibit a transcriptional alteration during PSTVd (31,32), C itrus viroid III (33), Peach latent mosaic viroid (34) and Citrus exocortis viroid (35) infections. Although all this experimental evidence may support the idea that viroid infection incites alterations in plant gene expression at transcriptional levels (13), viroid-induced methylation of the host gene(s) or disruption of methylation pathways (which may eventually result in symptom expression) has not yet been reported in natural infections (3).…”
Section: Introductionmentioning
confidence: 99%
“…In citrus plants, it has been clearly shown that symptoms are differently expressed in multiple viroid infections, with synergistic and antagonistic effects between CVds (Verniere et al, 2006;Serra et al, 2008). There may also be a synergistic interaction between viroids and viruses, as already described in peach (Herranz et al, 2013). It has been clearly shown that CBCVd is involved in the new severe disease of hop plants, although a synergistic action of CBCVd with HLVd cannot be ruled out.…”
Section: Discussionmentioning
confidence: 92%